Implementasi Program Tausiah Setelah Shalat Dhuha dalam Peningkatan Penguasaan Materi Pendidikan Agama Islam di SMP Muhammadiyah 07 Medan - Yulianisa; Ibrahim Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the implementation of the post-Dhuha prayer sermon program conducted by students in improving their mastery of Islamic religious education materials at Muhammadiyah Junior High School 07 in Medan. The research method employed in this study is qualitative research, with data collection techniques conducted through observation, involving a systematic, objective, logical, and rational data collection process. In this research, the process and meaning are emphasized using theoretical foundations as a guide to focus on research based on existing facts in the field. The research was conducted at Muhammadiyah Junior High School 07 in Medan. From the results of the research conducted by the researcher, it can be concluded that this program is conducted every day, for 15 minutes after the Dhuha prayer. The program is carried out by students in turns for each class, starting from class VII to class IX. This activity is also supervised and guided by rotating duty teachers, along with Islamic Education subject teachers. The implementation of the Post-Dhuha Prayer Sermon Program in Improving the Mastery of Islamic Religious Education Materials at Muhammadiyah Junior High School 07 in Medan has been well executed. Each student also gains additional knowledge and becomes more understanding of the Islamic religious education materials taught by their Islamic Education teachers in each class.